PLANT CULTIVATION, SCALED UP PREPARATION AND BIOLOGICAL TESTING OF NON ETHANOLIC EXTRACTS OF PELARGONIUM SIDOIDES DC - Kayser, O.; Kohnen, W.; Nyhuis, L.; van Breda, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Ethanolic extracts of Pelargonium sidoides DC and Pelargonium reniforme CURT are used for the production of the market authorized herbal remedy Umckaloabo®. In various studies related ethanolic extracts have been proven to be successful for high activity against upper airway infections. As most relevant constituents a variety of highly oxygenated coumarins, diverse phenolic compounds and hydrolysable and condensed tannins have been identified and tested. Despite its documented safe use in clinical studies, there has been a debate about the application of ethanolic extracts on children as one target group for ethanolic extract prescription. In this study we have invented an extraction protocol using PEG400, sorbitol, glycerol and water to produce phytoequivalent extracts with remaining high biological activities in the claimed therapeutic fields (1). Extracts were prepared from sustainable cultivated plants by industrially scaled up percolation of root material from three different batches and the qualitative and quantitative profile was determined by HPLC-UV/DAD and HPLC-MS. In non ethanolic PEG extracts the same metabolite profile as it is known in ethanolic extracts was confirmed based on scopoletin and umckalin as reference compounds. To validate biological activity and equivalency non ethanolic extracts were tested against S. aureus, H. influenzae, P. mirabilis, and E. coli. All extracts showed moderate antimicrobial activity. In extended immunemodulating assays interleukin-like activity has been demonstrated in macrophages infected with L. donovani as an intracellular parasite. Reference: [1] Kohnen, W. (2007) Verfahren zur Extraktion von Wurzeln der Pflanzengattung Pelargonium, danach hergestelltes Extrakt und Verwendung desselben, DE 2005 034227 A1